The contemporary English chronicles of the Wars of the Roses - Embree, Dan; Tavormina, M. Teresa (Mary Teresa), 1951- (Medieval chronicles, 2019)
The eight chronicles edited here are the principal surviving historical narratives of the Wars of the Roses written in English by men who lived through those wars. These are the best accounts by commoners (and one lord) written for their fellow Englishmen, produced within a few years of the events they describe, and have a particular immediacy. Five of these chronicles recount in detail particular events: The First Battle of St Albans (21-23 May 1455) and The Siege of Bamburgh Castle (June-July 1464) (batttles);The Rebellion in Lincolnshire (March 1470), and The History of the Arrival of King Edward IV (March-May 1471) (campaigns); and The Manner and Guiding of the Earl of Warwick (22-30 July 1470) (negotiations). The remaining three describe the development of the larger conflict over extended periods: the Continuation of Gregory's Chronicle (1450-69), Howard's Chronicle (1461-70), and Warkworth's Chronicle (1461-74). They do not cover the last stages of the Wars of the Roses, since by the end of May 1471, it must have looked as if the conflict was permanently resolved. These accounts, although contemporary, have to be treated with caution. All of them are narratives of public events intended for public consumption. They remain, however, vibrant and immediate accounts of the events they describe in a systematic, modern edition